1998
DOI: 10.1002/pro.5560070801
|View full text |Cite
|
Sign up to set email alerts
|

All in the family: Structural and evolutionary relationships among three modular proteins with diverse functions and variable assembly

Abstract: The crystal structures of three proteins of diverse function and low sequence similarity were analyzed to evaluate structural and evolutionary relationships. The proteins include a bacterial bleomycin resistance protein, a bacterial extradiol dioxygenase, and human glyoxalase I. Structural comparisons, as well as phylogenetic analyses, strongly indicate that the modem family of proteins represented by these structures arose through a rich evolutionary history that includes multiple gene duplication and fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
99
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(101 citation statements)
references
References 51 publications
1
99
0
1
Order By: Relevance
“…The discovery of the cupin superfamily epitomizes the value of an integrated approach to the study of protein structure and function (24,38,119,286). Only by such integration of information available from the previous X-ray analysis of storage proteins (155,177) with data from the prokaryotic genome programs was it possible to detect the evolutionary connection between this wide spectrum of enzymes and binding proteins and thereby to reinforce the concept that there is only a relatively small number of structurally conserved elements from which all proteins are constructed (271).…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…The discovery of the cupin superfamily epitomizes the value of an integrated approach to the study of protein structure and function (24,38,119,286). Only by such integration of information available from the previous X-ray analysis of storage proteins (155,177) with data from the prokaryotic genome programs was it possible to detect the evolutionary connection between this wide spectrum of enzymes and binding proteins and thereby to reinforce the concept that there is only a relatively small number of structurally conserved elements from which all proteins are constructed (271).…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Recent reports have identified additional Ni 2+ -activation class Glo1 enzymes in plant systems, including single subunit enzymes of the same size as the S. cerevisiae and the P. falciparum Glo1 (76-79). These findings are being actively studied with respect to stress response systems in agricultural important crops, and should prove extremely important in addressing the An additional aspect to the overall molecular structure of the Glo1 enzymes is that their protein fold is shared by other proteins in its structural class (βαβββ structural superfamily) yet these proteins exhibit a range of biological activities (54,80,81). Each protein subunit from a homodimeric Glo1 enzyme such as that from H. sapiens or E. coli is composed of two βαβββ structural domains.…”
Section: +mentioning
confidence: 99%
“…For the extended single chain Glo1 from S. cerevisiae and P. falciparum, based on protein homology modeling, four βαβββ domains are likely present. It has been proposed that the evolution of new structures and functions within this protein family likely arose from a combination of horizontal gene transfer and gene fusion events and possibly gene duplication events (79,81). The possibility of three-dimensional domain swapping has also been proposed (52,54).…”
Section: +mentioning
confidence: 99%
“…For example, the residues involved in Fe ϩ2 coordination in extradiol dioxygenase (E.C.1.13.11.39) (H146, H210, and E260) superimposed within 0.7-1.4 Å (C␣ atoms) of the Zn ϩ2 coordinating residues in glyoxalase I (Q33, E99, H126, E172) (E.C.4.4.1.5). 2,7 However, PA2721 is unlikely to bind metal ions because superimposition of PA2721 with these enzymes using the SSM server showed that residues H35, G146, F76, E117 occupy equivalent positions. 8 These residues are unlikely to provide a good environment for metal ion coordination.…”
mentioning
confidence: 99%
“…The structure was determined by SAD phasing using autoSHARP and refined against the peak data with REFMAC5. 2,15 The initial model was autotraced with 1.6 Å data using the program ARP/wARP. 16 The partial model obtained from ARP/wARP was subsequently manually extended, and rebuilt with O and COOT.…”
mentioning
confidence: 99%